Measurement of pesticide residues from chemical control of the invasive Spodoptera frugiperda (Lepidoptera: Noctuidae) in a maize experimental field in Mokwa, Nigeria - Togola, A.; Meseka, S.K.; Menkir, A.; Badu-Apraku, Baffour; Boukar, O.; Tamo, Manuele; Djouaka, R. (MDPI, 2018)
The management of the fall armyworm Spodoptera frugiperda in maize field necessitates the use a big quantities of insecticides and sometimes the use of multiple types and formulations of chemicals. The use of insecticides in crops is associated with environmental risks and health hazards to both producers and consumers. This study was designed to evaluate the residue of 11 insecticides that were used to control high population of the fall armyworm in maize field in Mokwa, Nigeria. Maize and soil samples were collected from an experimental field to investigate the residue level using high performance liquid chromatography (HPLC, Agilent Technologies, Santa Clara, CA, USA) analysis techniques. Results revealed the presence of five insecticide compounds (Cypermethrin, Deltamethrin, Lambda-Cyhalothrin, Permethrin, and Chorpyrifos) in soil samples with possible adverse effects on soil born organisms and other non-targeted species. In contrast, no residue was found in maize stems and seeds. From these results, we conclude that the treated maize remains safe for consumption and the producers may not get any serious risk of contamination from the chemical control of the fall armyworm